2001
DOI: 10.1046/j.1471-5740.2001.00020.x
|View full text |Cite
|
Sign up to set email alerts
|

Perceived temperature effects on microwave heated meals and meal components

Abstract: Two experiments were carried out to evaluate the effect of serving temperature on the pleasantness of microwave heated ready meals and meal components. Serving temperature clearly affected sensory attributes and the pleasantness of the meal components. However, while instrumental measurements had indicated large differences in temperatures between two microwave heated ready meals with different arrangement of meal components, the consumer panel perceived only small differences in some sensory attributes. Regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 8 publications
1
11
2
Order By: Relevance
“…Spiciness and deviation from the just-right serving temperature predicted hedonic ratings of main dishes to some extent. Earlier research has shown that serving temperature has great impact on overall pleasantness of meal components (Ryynänen, Tuorila, & Hyvönen, 2001), but in hot dishes of the present study, the deviation from just-right may not have been significant to the extent that it could lessen the experience but in a few cases. It is possible that the just-right ratings were attributions (Hewstone, 1983) rather than independent observations, thus used to justify hedonic ratings and express or confirm a consistency between elements of behavior.…”
Section: Acceptance and Sensory Profiling Of Main Dishescontrasting
confidence: 68%
“…Spiciness and deviation from the just-right serving temperature predicted hedonic ratings of main dishes to some extent. Earlier research has shown that serving temperature has great impact on overall pleasantness of meal components (Ryynänen, Tuorila, & Hyvönen, 2001), but in hot dishes of the present study, the deviation from just-right may not have been significant to the extent that it could lessen the experience but in a few cases. It is possible that the just-right ratings were attributions (Hewstone, 1983) rather than independent observations, thus used to justify hedonic ratings and express or confirm a consistency between elements of behavior.…”
Section: Acceptance and Sensory Profiling Of Main Dishescontrasting
confidence: 68%
“…The industrial setting up of microwave heating processes, nevertheless, faces two major issues. There is a non-uniform temperature distribution inside food product, creating temperature gradients within the product and resulting in hot and cold spots within the food matrix, moreover energy costs are high [119].…”
Section: Microwave Heatingmentioning
confidence: 99%
“…The effect of serving temperature on flavour perception depends on the food and the sensory attribute evaluated. Ryynänen, Tuorila, and Hyvönen (2001) reported an increase in both the odour and flavour intensities with serving temperature in different meals components, including meat patties.…”
Section: Introductionmentioning
confidence: 98%